Development of a Biological Bread - Mele, Susana (2013)
The objective of this work was to develop a wheat biological bread with good textural and sensorial characteristics, using biological ingredients, such as usual and certified biological yeasts and biological salt varying the added amounts to the dough. Several experiences were also done to find the most appropriate processing stages until establishing the best operation conditions. The optimized product was characterised considering the chemical and physical properties. This bread presented similar chemical characteristics to other wheat breads, with similar energetic value (232.8 Kcal/100g). The L colour parameter is high both in crust and loaf, with predominance of red and yellow colorations. It showed high elasticity and high alveoli percentage (about 25%). The global sensorial appreciation was 6.2 in a maximum scale of 10.